2019
DOI: 10.1080/02650487.2019.1634898
|View full text |Cite
|
Sign up to set email alerts
|

Celebrity vs. Influencer endorsements in advertising: the role of identification, credibility, and Product-Endorser fit

Abstract: In their marketing efforts, companies increasingly abandon traditional celebrity endorsers in favor of social media influencers, such as vloggers and Instafamous personalities. The effectiveness of using influencer endorsements as compared to traditional celebrity endorsements is not well understood. Therefore, the present research investigated the impact of celebrity vs. influencer endorsements on advertising effectiveness (attitudes toward the advertisement and product, and purchase intention), moderated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
772
6
50

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 910 publications
(863 citation statements)
references
References 41 publications
35
772
6
50
Order By: Relevance
“…It is suggested that a highly likeable and credible celebrity can form constructive consumers' attitude, which can further affect the behavioural intention [44,67,68]. It is also confirmed from the current literature that celebrity endorsement brings a significant and direct effect on the purchase intention [49,[59][60][61][62]69]. Based on the above discussions, the next hypothesis suggests that: Hypothesis 3a.…”
Section: Attitude Towards Celebrity Endorsement and Purchase Intentionmentioning
confidence: 67%
See 1 more Smart Citation
“…It is suggested that a highly likeable and credible celebrity can form constructive consumers' attitude, which can further affect the behavioural intention [44,67,68]. It is also confirmed from the current literature that celebrity endorsement brings a significant and direct effect on the purchase intention [49,[59][60][61][62]69]. Based on the above discussions, the next hypothesis suggests that: Hypothesis 3a.…”
Section: Attitude Towards Celebrity Endorsement and Purchase Intentionmentioning
confidence: 67%
“…Familiarity within the context of celebrity endorsement suggests consumers' knowledge regarding the celebrity and show how much they are familiar to the celebrity [60][61][62]. Previous research by using the relevant construct, i.e., brand, has proved that when the consumers are familiar with the brand, they will show a positive attitude and confidence towards the brand.…”
Section: Celebrity Familiariry and Celebrity Endorsementmentioning
confidence: 99%
“…Influencer marketing has a great meaning as an effective branding strategy and in their marketing efforts, companies increasingly abandon traditional celebrity endorsers in favour of social media influencers, such as vloggers and instafamous personalities [14,15]. The companies should also remember that engaging an influencer in the promotion process does not automatically mean people's trust in the quality of the product.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…People are continuously exposed to an overload of unhealthy food appeals in their physical as well as online environment. During the last decade, sharing online video content on YouTube and other social media platforms like Facebook and Instagram has become increasingly popular (Schouten, Janssen, & Verspaget, 2020). Following other people on online platforms has become a daily activity among millions of people worldwide (Lin, Bruning, and Swarna, 2018).…”
Section: Introductionmentioning
confidence: 99%